Discovering and documenting Acari: the first twenty years in Zootaxa - Zhang, Zhi-Qiang; Schatz, Heinrich; Pfingstl, Tobias; Goldschmidt, Tom; Martin, Peter; Pešić, Vladimir; Ramírez, Marcia; Schmidt, Karl-Heinz; Fan, Qing-Hai; Mironov, Sergey; Seeman, Owen; Halliday, Bruce (Zootaxa, 2021)
Acari represent the most diverse group within the arachnids with some 60,000 described species. It is generally believed that most species of mites are waiting to be discovered and described. Zootaxa was the most important journal for mite taxonomy during the last twenty years (2001 to 2020). It published 1305 papers by 1057 authors during these two decades, with descriptions of 3271 new taxa/names, which account for 24.4% of the total indexed in Zoological Record. The numbers of new synonyms of Acari in Zootaxa (334) also accounted for nearly a quarter (24.9%) of the total published during this period. These data indicate that Zootaxa has been an important and leading journal for acarologists to document the diversity of mites and ticks in the world.